Spatiotemporal Regulation of CRISPR/Cas9 Enables Efficient, Precise, and Heritable Edits in Plant Genomes - Rahman, Farhanur; Mishra, Apurva; Gupta, Archit; Sharma, Rita (Frontiers in Genome Editing, 2022)
CRISPR/Cas-mediated editing has revolutionized crop engineering. Due to the broad scope and potential of this technology, many studies have been carried out in the past decade towards optimizing genome editing constructs. Clearly, the choice of the promoter used to drive gRNA and Cas9 expression is critical to achieving high editing efficiency, precision, and heritability. While some important considerations for choosing a promoter include the number and nature of targets, host organism, mode of transformation and goal of the experiment, spatiotemporal regulation of Cas9 expression using tissue-specific or inducible promoters enables higher heritability and efficiency of targeted mutagenesis with reduced off-target effects. In this review, we discuss specific studies that highlight the prospects and trade-offs associated with the choice of promoters on genome editing and emphasize the need for inductive exploration and discovery to further advance this area of research in crop plants.